Changes in Phytochemicals and Determination of Optimum Fermentation Time during Black Tea Manufacturing - Rahman, M. M.; Hossain, M. M.; Das, R.; Ahmad, I. (Journal of Scientific Research, 2020)
Black tea processing consists of four steps, namely withering, CTC, fermentation and drying, while cup quality made tea mostly controlled by fermentation step. This study evaluated biochemical changes at different stages of black tea processing in Bangladesh and determined the optimum fermentation time. Samples were collected from different tea processing stages to measure major phytochemicals and time intervals during fermentation to measure theaflavins and thearubigins ratio. Caffeine content was the least susceptible to processing steps. Biochemical changes started at withering, cell maceration and enzymatic oxidation started at CTC processing, thus the major reduction in the reducing sugar (20.46 to 04.95 ppm), catechin (16.88 to 7.95 ppm) and polyphenol (42.30 to 30.73 ppm) occurred here. The significant changes appeared during fermentation when polyphenol content decreased from 44.66 to 18.23 and catechin from 17.41 to 03.98 ppm due to the breakdown of these compounds to theaflavins (TF) and thearubigins (TR). The TF and TR ratio increased with fermentation time, and the highest of 1:8.4 was found at 50 min, which turned into 1:10 in the final product. The made tea quality parameters were comparable or better at fermentation time of 50 min than the quality of the black tea available in market.